A personal leadership statement (2023)
In multigenerational English classrooms, teachers face the challenge of helping both younger and older learners excel in a foreign language. Leadership is crucial in terms of recognizing, adapting, and creatively handling specific needs according to the age group. This paper explores how adaptive leadership function, emphasizing the role of open-minded leaders who are motivated and involved to provide meaningful changes in the student’s learning process. This statement guides teachers to analyze the learning styles based on students’ diversity. Thus, this paper proposes through the adaptive leadership assumptions, implications, and empowerment a guide for teachers to navigate various age groups successfully. The aim is to foster an environment where positive changes happen, enhancing English language skills.